Reliability and validity of low cost pressure gauge manometer for measurement of respiratory muscle strength in healthy children: a cross-sectional study - Sundararajan, Swathi; Afle, Gauri Mayank (International Journal Of Community Medicine And Public Health, 2023)
Background: Assessing respiratory muscle strength is an important aspect for clinical practice as well as in research. Multiple factors such as health status of an individual, level of physical fitness and postsurgical recovery of an individual have an influence on respiratory biomechanics. Respiratory muscle strength is determined by measuring maximal inspiratory pressure and maximal expiratory pressure. There is a need for a cost effective, portable, easy to build device specifically to estimate respiratory muscle strength. There is insufficient literature regarding the resources used to determine the respiratory muscle strength testing in children, hence this study aims to establish the reliability and validity of low cost pressure gauge manometer which could be a useful tool in measuring respiratory muscle strength in children. Methods: A capsule sensing pressure gauge constructed according to the American thoracic society guidelines with a calibration of pressure between −200 cmH2O to +200 cmH2O. It was used to measure the respiratory muscle strength. The study was conducted on 300 healthy children. Results: SPSS software was used for statistical analysis. Reliability of 0.92 and 0.97 was obtained for MIP and MEP respectively by test retest method. Construct validity index showed a validity score of 0.8 for MIP and MEP. Conclusions: The results indicate that the low cost pressure gauge manometer can be used as a reliable and valid device to measure respiratory muscle strength in children.